2016
DOI: 10.1073/pnas.1613428113
|View full text |Cite
|
Sign up to set email alerts
|

Precise gene editing paves the way for derivation of Mannheimia haemolytica leukotoxin-resistant cattle

Abstract: Signal peptides of membrane proteins are cleaved by signal peptidase once the nascent proteins reach the endoplasmic reticulum. Previously, we reported that, contrary to the paradigm, the signal peptide of ruminant CD18, the β subunit of β2 integrins, is not cleaved and hence remains intact on mature CD18 molecules expressed on the surface of ruminant leukocytes. Leukotoxin secreted by Mannheimia (Pasteurella) haemolytica binds to the intact signal peptide and causes cytolysis of ruminant leukocytes, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…These observations were translated to bovine clinical research in a subsequent publication in which a bovine fetus was genetically engineered to express the mutated CD18 allele. Leukocytes isolated from this fetus are resistant to LktA cytolytic activity and provide promise to the potential to genetically engineer cattle that are resistant to Mannheimia haemolytica pneumonia [58]. This in vivo demonstration of the importance of CD18 alone provides strong support for the publications described above which conclude that CD18 alone is the critical binding partner for LktA cytolytic activity.…”
Section: Lktasupporting
confidence: 57%
“…These observations were translated to bovine clinical research in a subsequent publication in which a bovine fetus was genetically engineered to express the mutated CD18 allele. Leukocytes isolated from this fetus are resistant to LktA cytolytic activity and provide promise to the potential to genetically engineer cattle that are resistant to Mannheimia haemolytica pneumonia [58]. This in vivo demonstration of the importance of CD18 alone provides strong support for the publications described above which conclude that CD18 alone is the critical binding partner for LktA cytolytic activity.…”
Section: Lktasupporting
confidence: 57%
“…Cows that are resistant to Mannheimia haemolytica toxemia have already been produced by replacing glutamine with glycine at position –5 (signal peptide) of the bovine CD18 molecule (Shanthalingam et al . ). Changes introduced by genome editing in germline cells or zygotes are heritable, but it can take many generations of editing to fix the favourable allele in livestock populations (Gonen et al .…”
Section: Pitfalls and Perspectivesmentioning
confidence: 97%
“…In particular, traits which improve animal health and welfare when altered using animal biotechnology may gain wider public acceptance since these are not only economically beneficial but also may prevent animal suffering. Many studies have been dedicated to the prevention of disease in cattle, for example protection against mastitis through the production of antimicrobial compounds such as lactoferrin, lysostaphin, and lysozyme [25] , prevention of bovine spongiform encephalopathy through mutation of the implicated PrP proteins [26] as well as resistance to Mannheimia hemolytica [27] and to bovine tuberculosis [13] . If it is demonstrated that these genetic alterations yield more disease resilient animals then these are likely candidates for future commercialization.…”
Section: Developments In Genetic Modification Of Cattlementioning
confidence: 99%